Virtue Locales: An Exploratory Study of a New Criminological Concept. Issue 2 (1st February 2023) - Boehme, Hunter M.
ABSTRACT: Place-based criminology largely centers on what and which areas attract or generate crime, with limited scholarly activity focused on which businesses/land uses prevent crime across spatial collectives. The current study proposes an original theoretical concept called "virtue locales" – which are race-specific land uses that reduce crime at the nearby area due to the virtuous effects these businesses provide to the community (e.g., social guardianship, place management, and social cohesion). Using a quasi-experimental design of street segments through propensity score matching, this study tests whether there are crime reducing effects of barbershops and beauty salons (virtue locales) in Columbia, South Carolina. Results from multiple count regression models show that street segments with barbershops and beauty salons (virtue locales) had lower crime counts than other streets with businesses, but no virtue locale. This finding remained in all areas of the city, regardless of racial composition. A number of policy, research, and theoretical implications are discussed.